2003
DOI: 10.1074/jbc.m302305200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in Support of a Docking Model for the Release of the Transcription Factor σF from the Antisigma Factor SpoIIAB in Bacillus subtilis

Abstract: Cell-specific activation of the transcription factor F during the process of sporulation in Bacillus subtilis is governed by an antisigma factor SpoIIAB and an antiantisigma factor SpoIIAA. SpoIIAB, which exists as a dimer, binds to F in a complex of stoichiometry F ⅐SpoIIAB 2 . Escape from the complex is mediated by SpoIIAA, which reacts with the complex to cause the release of free F . Previous evidence indicated that Arg-20 in SpoIIAB is a contact site for both F and SpoIIAA and that contact with F is media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 23 publications
6
63
1
Order By: Relevance
“…Several structures of AB in complex with AA have now been solved [35]. These data provided structural evidence for the previously proposed docking model [34,36] that describes how AA induces σ F release from the σ F /AB complex ( Figure 2a). In this model, one AB protomer of the asymmetric σ F /AB 2 complex (AB1 of Figure 2a; for more details see Figures 7 and 9 of ref.…”
Section: Regulation Of σ F Activity During Sporulationmentioning
confidence: 51%
“…Several structures of AB in complex with AA have now been solved [35]. These data provided structural evidence for the previously proposed docking model [34,36] that describes how AA induces σ F release from the σ F /AB complex ( Figure 2a). In this model, one AB protomer of the asymmetric σ F /AB 2 complex (AB1 of Figure 2a; for more details see Figures 7 and 9 of ref.…”
Section: Regulation Of σ F Activity During Sporulationmentioning
confidence: 51%
“…Experiments were performed with SpoIIAB heterodimers consisting of wild-type SpoIIAB and SpoIIABR20E, a mutant deficient in binding SpoIIAA (92). The experiments revealed that SpoIIAA interacted with the molecule of SpoIIAB not bound to F and induced release of F from the other SpoIIAB molecule, most likely by steric displacement (115). Another interesting result from this study was that a mutant of SpoIIAB deficient in its kinase activity (SpoIIABR105A) resulted in excessive levels of F activity.…”
Section: Mechanisms Of Compartmentalizationmentioning
confidence: 91%
“…Moreover, our analysis indicates that RsbT utilizes a highly overlapped set of amino acids in the N-terminal domains of both RsbR and RsbU, albeit with different chemical characteristics, to form its alternative complexes. (49,50). Therefore, one copy of SpoIIAB Arg 20 is always available for SpoIIAA to gain a "toehold" on SpoIIAB inducing release of F .…”
Section: Arg23mentioning
confidence: 99%